An Integrative Approach to Ketamine Therapy May Enhance Multiple Dimensions of Efficacy: Improving Therapeutic Outcomes With Treatment Resistant Depression - Muscat, Sherry-Anne; Hartelius, Glenn; Crouch, Courtenay Richards; Morin, Kevin W. (Frontiers in Psychiatry, 2021)
Research over the last two decades has established ketamine as a safe, effective, fast-acting, and sustained antidepressant that significantly reduces adverse symptoms associated with depression, even in patients who are treatment resistant. Much of this research has evolved within the framework of several independent branches of scientific inquiry: in addition to the study of ketamine as a noncompetitive NMDAR antagonist with rapid antidepressant effects, it has also been found effective as a psychoplastogen that stimulates synaptogenesis and increases neuroplasticity, as a powerful anti-inflammatory that may improve inflammation-related depressive symptoms, as a substance that induces beneficial high entropy brain states, and as a subjectively impactful psychedelic agent. Each branch of inquiry has generated independent evidence of ketamine’s efficacy but has advanced without substantive coordination or communication with other lines of inquiry. Integrative research that considers these branches of research together may lead towards a better understanding of ketamine’s effects and improved treatment protocols and clinical outcomes. Such an overview can inform more comprehensive patient care through: a) informed patient psychoeducation that encompasses all of ketamine’s mechanisms of action; b) calibration of optimal dosage to ensure induction and maintenance of high entropy brain states during each ketamine session utilizing EEG measurement; c) Improved management of emergence side effects through proper care for set and setting; d) inclusion of pre selected appropriate music to enhance the emotional experience; (e) increased monitoring of ketamine effects on cortical activity, inter-hemispheric imbalance, and inflammation-related levels of cytokines to further improvements in ketamine protocols; and (f) appropriate timing of any adjunctive psychotherapy sessions to coincide with peak neurogenesis at 24–48 hours post ketamine treatment.